Whose Governance, Which Legitimacy? Myanmar’s Collective Agency in a Domineering Framework on the Rohingya Crisis - Kevin Ali Sesarianto (Intermestic: Journal of International Studies, 2021)
July of 2017 is the last time the United Nations special rapporteur was allowed into Myanmar to report on the Rohingya crisis. By contrast, the Foreign Minister of Indonesia was well-received to talk about the same problem in 2017. This article sees the problem as a legitimacy crisis: Myanmar did not see the United Nations intervention framework to report on the Rohingya crisis as legitimate due to the perceived lack of the former’s agency in that framework. This article uses the concept of collective agency to further understand Myanmar’s reception of the United Nations regarding the Rohingya crisis. Myanmar’s rationality – way of seeing things – is seen to be marginalised and even deleted by the United Nations’ internationalist/cosmopolitan rationality through labels such as ‘draconian’ and ‘stagnant’ Indonesia’s approach is more sensitive to Myanmar’s agency. This article concludes that the exclusionist practice by the United Nations makes the framework lose its support-worthiness.